Microvascular Dysfunction in Heart Failure With Preserved Ejection Fraction - D’Amario, Domenico; Migliaro, Stefano; Borovac, Josip A.; Restivo, Attilio; Vergallo, Rocco; Galli, Mattia; Leone, Antonio Maria; Montone, Rocco A.; Niccoli, Giampaolo; Aspromonte, Nadia; Crea, Filippo (Frontiers in Physiology, 2019)
Heart failure with preserved ejection fraction (HFpEF) is an increasingly studied entity accounting for 50% of all diagnosed heart failure and that has claimed its own dignity being markedly different from heart failure with reduced EF in terms of etiology and natural history (Graziani et al., 2018). Recently, a growing body of evidence points the finger toward microvascular dysfunction as the major determinant of the pathological cascade that justifies clinical manifestations (Crea et al., 2017). The high burden of comorbidities such as metabolic syndrome, hypertension, atrial fibrillation, chronic kidney disease, obstructive sleep apnea, and similar, could lead to a systemic inflammatory state that impacts the physiology of the endothelium and the perivascular environment, engaging complex molecular pathways that ultimately converge to myocardial fibrosis, stiffening and dysfunction (Paulus and Tschope, 2013). These changes could even self-perpetrate with a positive feedback where hypoxia and locally released inflammatory cytokines trigger interstitial fibrosis and hypertrophy (Ohanyan et al., 2018). Identifying microvascular dysfunction both as the cause and the maintenance mechanism of this condition has opened the field to explore specific pharmacological targets like NO pathway, sarcomeric titin, TGF-b pathway, immunomodulators or adenosine receptors, trying to tackle the endothelial impairment that lies in the background of this syndrome (Graziani et al., 2018;Lam et al., 2018). Yet, many questions remain and the new data collected still lack a translation to improved treatment strategies. To further elaborate on this tangled and exponentially growing topic we will review the evidence favoring a microvasculature-driven etiology of this condition, its clinical correlations, the proposed diagnostic workup and the available/ hypothesized therapeutic options to address microvascular dysfunction in the failing heart.